Exploring Effective Communication Skills among Local and International Civil Engineering Undergraduates: A Case Study - Sarala Thulasi Palpanadan; Khaireen Layla Mohd Hilmi (Development in Language Studies, 2024)
This study focuses on issues faced by local and foreign undergraduates in communicating in English effectively in a public university in Malaysia. Apparently, there seems to be a gap in effective communication between the local students and the foreign students in speaking in English. This gap disrupts a smooth flow of discussion and understanding between the two groups of students during the course of learning while studying including lectures, lab activities, and projects. Therefore this study was conducted to identify the issues faced by the local and foreign undergraduates speaking in English to enhance the effectiveness of their communication. This case study was conducted by interviewing 10 participants comprising local and foreign. The thematic analysis highlighted three main issues including clarity, academic success, and cultural exchange. The findings also highlighted that the students perceived pronunciation and intonation as important aspects of communicating effectively. This study hopes to be an eye-opener to individuals and institutions with local and foreign students to be more aware of the effective use of English language circumstances within the diverse classroom environment.